Development of Online Learning Videos Using Animiz Software on Hydrocarbon Topics - Arnanda Irawan; Agus Kamaludin (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2022)
Animated videos as interactive learning media are rarely made using animation software. The study aims to develop online learning videos using Animiz Animation Maker Software on hydrocarbon material and analyze video quality based on assessing material experts, media experts, reviewers, and student responses. The research is development research (R&D) with development model consisting of the define, design, develop, and disseminate stages, but is limited to the developing stage. The final product is an animated video of hydrocarbon topics. The result of product quality assessment by material experts, media experts, and reviewers, respectively 84%, 95%, and 87% with very good category. The video was responded positively by students with an ideal percentage of 97%. Based on the assessment results, this learning video can be used as alternative chemistry learning media for online learning.